Perbandingan Hasil Belajar PAI Antara Siswa Lulusan Madrasah Tsanawiyah (MTs) dan Sekolah Menengah Pertama (SMP) Kelas X di SMAN 1 Banuhampu - Mutiara Alina; Wedra Aprison; Salmi Wati; Muhiddinur Kamal (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This research was motivated by the discovery that students who graduated from Junior High School (SMP) were more active and superior than students who graduated from Madrasah Tsanawiyah (MTs) in Islamic Education learning. This is of course a problem, because basically, in PAI learning, students who graduate from Madrasah Tsanawiyah (MTs) must be superior to students who graduate from Junior High Schools (SMP) because students who graduate from Madrasah Tsanawiyah (MTs) are students with notaben educational backgrounds religion school. This is of course a problem that must be resolved. So this research aims to compare the PAI learning outcomes of the two graduates and see how comparable they are. The type of research used in this research is comparative with a quantitative approach. The population is all class The sample in this study used a cluster random sampling technique, and 4 classes were sampled, with details of 36 MTs graduate students and 71 junior high school graduate students. Data was collected through documentation and analyzed independent sample t tests. Based on the results of research that has been carried out, research results show that there is a comparison of student PAI learning outcomes between MTs and SMP graduates, which is proven by the results of the independent sample t test where the calculated t value > t table is 8.332 > 1.985. And student PAI learning outcomes are higher for MTs graduate students as evidenced by the mean difference value in the independent sample t test of 7.329, which means that MTs graduate students have an average PAI learning outcome score of 7.329 higher than the PAI learning outcomes of junior high school graduate students so that Ha accepted.